2018
DOI: 10.1183/23120541.00155-2017
|View full text |Cite
|
Sign up to set email alerts
|

Narrative medicine educational project to improve the care of patients with chronic obstructive pulmonary disease

Abstract: Chronic obstructive pulmonary disease (COPD) is characterised by a progressive loss of pulmonary function. Often patients do not adhere to inhaled therapies and this leads clinicians to switch treatments in order to improve control of the symptoms. Narrative medicine is a useful approach that helps healthcare professionals to think over the doctor–patient relationship and how patients live with their disease. The aim of this training project was to teach pulmonologists the basics of narrative medicine: to care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…Furthermore, the collected narratives represented a precious tool to express and give space to considerations and emotions in relating with patients-illness centred narratives-which in the ordinary professional settings can be repressed, contributing to increase the levels of stress. Indeed, the positive effect of the narrative medicine approach on daily practice and professional quality of life, preventing burnout, has been shown [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the collected narratives represented a precious tool to express and give space to considerations and emotions in relating with patients-illness centred narratives-which in the ordinary professional settings can be repressed, contributing to increase the levels of stress. Indeed, the positive effect of the narrative medicine approach on daily practice and professional quality of life, preventing burnout, has been shown [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is interesting to notice that the complexity of the treatment plan was considered more burdensome by the physicians than by either the patient or their caregiver. A recent study in patients with COPD demonstrated a link between the physicians’ style of writing about their relationship with patients and the quality of care of their patients [ 28 ]. In that study, participating physicians wrote illness-centered narratives.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to explore patient understanding regarding specific vaccinations and address any concerns they might have. Recent research has shown that using a narrative medicine (patient-centred) approach, which focusses on cultivating “positive patient-doctor relationships based on listening and understanding”, can improve adherence to treatment recommendations in patients with COPD [40].…”
Section: Discussionmentioning
confidence: 99%